Prognostic impact of beta-blocker compared to combined amiodarone therapy secondary to ventricular tachyarrhythmias. (15th February 2019) - Schupp, Tobias; Behnes, Michael; Reiser, Linda; Bollow, Armin; Taton, Gabriel; Reichelt, Thomas; Ellguth, Dominik; Engelke, Niko; Ansari, Uzair; El-Battrawy, Ibrahim; Bertsch, Thomas; Weiß, Christel; et al.
Abstract: Objective: The study sought to assess the prognostic impact of treatment with beta-blocker (BB) compared to combined BB plus amiodarone (BB-AMIO) on long-term survival in patients surviving ventricular tachyarrhythmias on admission. Background: Data regarding the prognostic outcome of patients presenting with ventricular tachyarrhythmias treated with BB and BB-AMIO is limited. Methods: A large retrospective registry was used including consecutive patients surviving index episodes of ventricular tachyarrhythmias from 2002 to 2016. Patients treated with BB were compared to patients with BB-AMIO. The primary prognostic endpoint was long-term all-cause death at 3 years. Kaplan-Meier, multivariable Cox regression and propensity score matching analyses were applied. Results: A total of 1354 patients was included, 85% treated with BB, 15% with BB-AMIO. Within the unmatched real-life cohort, uni- and multivariable Cox regression models revealed BB associated with improved long-term survival compared to BB-AMIO (univariable: HR = 0.550; p = 0.001, multivariable: HR = 0.712; statistical trend, p = 0.052). After propensity-score matching ( n = 186 matched pairs), BB therapy was still associated with improved survival compared to BB-AMIO (mortality rate 18% versus 26%; log rank p = 0.042; HR = 0.634; 95% CI = 0.407–0.988; p = 0.044). Prognostic superiority of BB was mainly observed in patients with LVEF ≥ 35% (HR = 0.463; 95% CI = 0.215–0.997; p = 0.049) and in those without atrial fibrillation (non-AF) (HR = 0.415; 95% CI = 0.202–0.852; p = 0.017). Conclusion: BB therapy is associated with improved secondary long-term prognosis compared to BB-AMIO in patients surviving index episodes of ventricular tachyarrhythmias. Highlights: The study evaluates the impact of sole beta-blocker (BB) vs. combined amiodarone (BB-AMIO) in patients with ventricular tachyarrhythmias. BB therapy was associated with improved long-term survival compared to BB-AMIO therapy. Prognostic superiority of BB therapy was observed in patients with LVEF ≥35% and in patients without atrial fibrillation.